Preparation method of multi-acid-group covalent organic framework modified diaphragm, modified diaphragm and lithium-sulfur battery

By using polyacid-based covalent organic framework modified separators in lithium-sulfur batteries, the ordered porous structure of TFPOT-POM and the catalytic activity of transition metals are solved, and the problems of polysulfide dissolution, low conductivity and structural damage during the circulation of lithium-sulfur batteries are achieved, achieving higher stability and electrochemical performance.

CN119764744AActive Publication Date: 2025-04-04JILIN NORMAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411895948.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-04
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

During the circulation process of lithium-sulfur batteries, there are problems such as polysulfide dissolution, low conductivity of sulfur and lithium sulfide, and structural damage caused by the expansion of sulfur volume, resulting in low discharge capacity and fast capacity decay.

Method used

The preparation method of polyacid-based covalent organic framework modified separator is adopted, and TFPOT-POM is synthesized as a separator material, and its ordered porous structure and transition metal catalytic activity are used to inhibit the shuttle of polysulfides and accelerate the electrochemical reaction.

Benefits of technology

It improves the stability and electrochemical performance of lithium-sulfur batteries, enhances ionic conductivity, inhibits the shuttle of polysulfides, extends the cycle life of the battery, and improves the charge and discharge efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764744A_ABST
    Figure CN119764744A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a multi-acid-group covalent organic framework modified diaphragm, the modified diaphragm and a lithium-sulfur battery, and belongs to the technical field of batteries, TFPOT-POM solid powder is synthesized by taking two monomers of 2, 4, 6-tri (4-formylphenoxy)-1, 3, 5-triazine (TFPOT) and (nBu4N) 3 [CoMo6O18 ((OCH2) 3CNH2) 2] (POM) as solutes, taking N, N-dimethylformamide as a solvent and taking trifluoroacetic acid as a catalyst, and then the TFPOT-POM solid powder is prepared into a lithium-sulfur battery diaphragm. And finally, preparing the TFPOT-POM precursor material, PVDF (Polyvinylidene Fluoride) and Super-P according to a limited proportion, so as to obtain the modified diaphragm. The TFPOT-POM has an ordered structure and efficient catalytic activity, and can improve the conduction rate of lithium ions in the diaphragm, thereby improving the charge-discharge efficiency of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a preparation method of a polyacid-based covalent organic skeleton modified diaphragm, a modified diaphragm and a lithium-sulfur battery. Background Art

[0002] Energy storage is an important component and key supporting technology of the new energy industry and has become one of the focuses of international energy technology strategic competition. Lithium-sulfur batteries are considered to be one of the most promising next-generation energy storage technologies due to their high energy density and low cost. The theoretical energy density of lithium-sulfur batteries is very high (2600Wh·kg −1 ), Li-S batteries can meet the growing global energy demand due to the high natural availability, affordability and environmental friendliness of sulfur; however, several important challenges hinder their commercial application. For decades, people have been working hard to address the obstacles of lithium-sulfur batteries to improve the sulfur electrochemical performance of lithium-sulfur batteries. Therefore, it is of great significance to develop lithium-sulfur batteries with high battery capacity and cycling stability.

[0003] The main problems with the positive electrode of lithium-sulfur batteries are: (1) polysulfides dissolve into the electrolyte. During the cycle, the intermediate long-chain lithium polysulfides (Li2S4 to Li2S8) are easily dissolved into the ether-based electrolyte, which leads to the continuous loss of active materials into the electrolyte. Some of them remain dissolved and will not precipitate back to the positive electrode in the form of lithium sulfide at the end of discharge. Therefore, low discharge capacity and rapid capacity decay are often observed during the cycle. (2) Sulfur and lithium sulfide have low conductivity. The insulating properties of sulfur and lithium sulfide in electrons and ions lead to poor utilization of active materials. During the discharge process, the precipitation of insulating lithium sulfide also leads to passivation of the cathode surface, thereby limiting the actual discharge capacity that can be achieved. (3) Sulfur expands greatly during the lithiation process. Due to the difference in density between sulfur and lithium sulfide (2.03 g cm -3 and 1.66 g·cm -3 ), sulfur will expand in volume by about 80% after being fully lithiated into lithium sulfide, which will lead to powderization and structural damage at the electrode level.

[0004] On the anode side, there are several issues that need to be overcome before lithium-sulfur batteries can be successfully commercialized: (1) the polysulfide shuttling effect, in which long-chain lithium polysulfides (Li2S4 to Li2S8) dissolved in the electrolyte can diffuse to the lithium anode for chemical reduction (rather than electrochemical reduction) to form low-order polysulfides, which then diffuse back to the sulfur cathode for re-oxidation. This polysulfide shuttling effect is essentially an internal short circuit, leading to self-discharge and low Coulombic efficiency during cycling; (2) the non-uniform solid electrolyte interface (SEI), in which lithium metal is highly reactive and reacts with the electrolyte to form SEI on the surface, which is ionically conductive but electronically insulating. However, in most cases, the SEI is non-uniform and cannot adequately passivate the lithium metal surface, resulting in continuous, undesirable side reactions with the electrolyte. This consumes both lithium metal and electrolyte, resulting in poor reversibility and low Coulombic efficiency during repeated electroplating and stripping. (3) The growth of lithium dendrites causes the SEI to continuously break and reform, further consuming lithium metal and electrolyte. This causes the battery to eventually fail due to electrolyte depletion and high impedance through the thick SEI.

[0005] To circumvent the above challenges, researchers have made great efforts to improve the electrochemical performance of LSBs, including constructing high-quality sulfur hosts, developing functional separators or interlayers, and optimizing electrolyte additives. Among the reported strategies, the design of functional separators is feasible, which can effectively suppress the shuttling of polysulfides to a certain extent and promote the rapid conversion of lithium polysulfides to improve the overall performance of LSBs. Currently, the modified materials can be divided into three categories: (1) carbon-based modifiers for physical confinement of soluble polysulfides, such as carbon nanotubes, graphene, and mesoporous carbon; (2) polar materials with strong affinity for polysulfides by chemical adsorption, such as heteroatom-containing polymers, metal oxides, and metal-organic frameworks; (3) transition metal-based materials for chemical adsorption and catalytic conversion of polysulfides, such as TiO2-Mxene, porous metal foams, metal-embedded carbon nanosheets, and metal-containing polymers. However, it should be pointed out that the use of a densifier layer can effectively suppress the shuttling of polysulfides, but it will cover the pore structure of the separator to a certain extent, thereby generating unnecessary impedance to the conduction of lithium ions. In addition, when polysulfides are adsorbed on the modified layer and converted into insoluble sulfur, the slow lithium ion diffusion kinetics may aggravate their reuse, leading to the loss of active materials and further blocking the pores in the separator. Therefore, it is crucial to develop functional layers on the separator to simultaneously achieve fast lithium ion conduction and polysulfide blocking.

[0006] Polyoxometalates are a class of polymetallic-oxygen cluster compounds with various shapes, high negative charge, strong redox ability, and easy grafting. They have been widely used in the field of electrochemistry due to their good proton transfer ability and catalytic activity. Density functional theory (DFT) calculations show that the redox potential of POMs is adjustable, which makes it possible to select and design suitable POMs for specific battery systems. Although researchers have connected POMs to carriers such as polymers, metal-organic frameworks (MOFs), covalent organic frameworks (COFs) or graphene through in situ synthesis, impregnation synthesis, and mechanical grinding synthesis, some remarkable results have been achieved in the fields of energy storage / conversion, electrocatalysis, etc.

[0007] Defects and shortcomings of the existing technology: There are still some urgent problems to be solved, such as the single function of the carrier, difficulty in functionalization, easy agglomeration, difficulty in forming a stable composite material with POMs, and defects such as easy loss and short service life during application. When polyacid materials are used in batteries, the inevitable agglomeration will bury the effective active sites of the polyacid, thereby limiting its adsorption or catalytic function on LiPSs. Although POMs can catalyze the reduction of elemental sulfur and the oxidation of Li2S, the POMs material reduced after lithium is easily dissolved in the electrolyte during the charge and discharge process, inevitably leading to the loss of POMs catalyst on the positive electrode side. This makes it difficult for such POMs materials to meet the social requirements of the growing energy demand. Summary of the invention

[0008] In view of the problems existing in the prior art, the present application proposes a method for preparing a polyacid-based covalent organic skeleton modified diaphragm, a modified diaphragm and a lithium-sulfur battery.

[0009] The preparation method of the polyacid-based covalent organic skeleton modified diaphragm comprises the following steps: S1. Synthesis of TFPOT-COF 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPOT) and polyoxometalate (POM) are placed in a Pyrex tube and mixed to obtain a mixed monomer, and then N,N-dimethylformamide solution is added, ultrasonically shaken, and then a catalyst is added and ultrasonically shaken, and then the freezing and vacuuming process is repeated three times, flame-sealed with butane gas, heated to obtain a solid product, and then washed and vacuum-dried to obtain TFPOT-POM; S2. Preparation of modified diaphragm TFPOT-POM, PVDF and Super-P were mixed and ball-milled for 1-1.5 hours to obtain a mixture; N-methylpyrrolidone solution was added to the mixture and ball-milled for 1-2 hours to obtain a slurry; the slurry was coated on the surface of PP, vacuum-dried, and the obtained diaphragm was cut into discs with a diameter of 16 mm to obtain a modified diaphragm.

[0010] The mass ratio of 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPOT) to polyoxometalate (POM) in step S1 is (2-6):25; The molecular formula of the polyoxometalate (POM) in step S1 is ( n Bu4N)3[CoMo6O 18 ((OCH2)3CNH2)2]; The amount of 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPOT) and N,N-dimethylformamide used in step S1 is: (1-8) mg / mL; The ultrasonic oscillation time in step S1 is 3-5 minutes; The catalyst in step S1 is trifluoroacetic acid, and the dosage of trifluoroacetic acid and 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPOT) is 0.001-0.0025 mL / mg; the mass fraction of the trifluoroacetic acid is not less than 99%; The heating temperature in step S1 is 100-140° C. and the heating time is 100-140 hours; The specific washing process in step S1 is: adding acetone and tetrahydrofuran solution in sequence and washing by alternating centrifugation for 3-5 times; The vacuum drying temperature in step S1 is 80-120°C, and the vacuum drying time is 10-12h; The weight ratio of TFPOT-POM, PVDF and Super-P in step S2 is 7:1:2; The vacuum drying temperature in step S2 is 60-80° C., and the vacuum drying time is 12-16 hours.

[0011] A polyacid-based covalent organic skeleton modified diaphragm obtained by the above preparation method.

[0012] A lithium-sulfur battery comprises a polyacid-based covalent organic skeleton modified diaphragm.

[0013] Compared with the prior art, the present invention has the following advantages: 1. The polyacid-based covalent organic framework TFPOT-POM was synthesized by a solvothermal method. By improving the catalytic ability of the covalent organic framework, the prepared TFPOT-POM exhibited good stability and high catalytic activity. As a membrane modification material for Li-S batteries, it can enhance the stability of the battery.

[0014] 2. TFPOT-POM has an ordered porous structure, which can improve the stability of polyacids in the electrolyte, thereby improving the charge and discharge efficiency of the battery; in addition, due to the presence of transition metals in the structure, the battery assembled from the TFPOT-POM modified intermediate layer has a higher ionic conductivity (1.99 mS·cm -1 The modified interlayer based on TFPOT-POM can not only inhibit the shuttling of polysulfides, but also accelerate the battery reaction process through transition metal catalytic oxidation of polysulfides; the TFPOT-POM battery also showed excellent electrochemical performance, with an initial specific capacity of 844 mAh g at 1 C. -1 The specific capacity after 500 cycles is 643 mAh g -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Schematic diagram of the synthesis process of the polymer TFPOT-POM of the present invention; Figure 2 is the XRD pattern of the polymer obtained in Example 1 of the present invention; Figure 3 is the XRD pattern of the polymer obtained in Comparative Example 1; Figure 4 is the XRD pattern of the polymer obtained in Comparative Example 2; Figure 5 is the XRD pattern of the polymer obtained in Comparative Example 3; Figure 6 is the XRD pattern of the polymer obtained in Comparative Example 4; Figure 7 The nitrogen adsorption-desorption analysis and pore size distribution diagram of the polymer obtained in Example 1 of the present invention are shown in FIG. Figure 7 (a) is the N2 adsorption-desorption isotherm of TFPOT-POM. Figure 7 (b) is the pore size distribution diagram of TFPOT-POM; Figure 8 This is the XPS graph of the polymer obtained in Example 1 of the present invention, wherein: Figure 8 (a) C 1s spectrum of TFPOT-POM; Figure 8 (b) N 1s spectrum of TFPOT-POM; Figure 8 (c) O 1s spectrum of TFPOT-POM; Figure 8(d) Co 2p spectrum before and after TFPOT-POM adsorbs Li2S6; Figure 8 (e) Mo 3d spectrum before and after TFPOT-POM adsorbs Li2S6; Figure 8 (f) S 2p spectrum of TFPOT-POM after adsorption of Li2S6; Fig. 9 This is a high-resolution scanning electron microscope image of the polymer obtained in Example 1 of the present invention, wherein: Fig. 9 (a) is the scanning electron microscope image of TFPOT-POM / PP. Fig. 9 (b) is the scanning electron microscope image of the polymer TFPOT-POM / PP after cycling; Fig. 9 (c) is a cross-sectional scan of the TFPOT-POM / PP separator; Fig.10 The catalytic performance diagram of the Li-S battery prepared by the present invention, wherein: Fig.10 (a) is the CV graph of TFPOT-POM and PP batteries; 10 (b) is the EIS graph of TFPOT-POM battery; Fig.10 (c) Conductivity diagram of TFPOT-POM and PP batteries; Fig.10 (d) Ion migration diagram of TFPOT-POM battery; Fig.10 (e) is the deposition experiment diagram of TFPOT-POM modified battery; Fig.10 (f) Symmetrical battery CV diagram of TFPOT-POM / PP and PP modified batteries; Fig.11 This is a performance diagram of the Li-S battery prepared by the present invention, wherein Fig.11 (a) is a three-cycle CV graph of the modified diaphragm prepared with TFPOT-POM obtained in Example 1; 11 (b) is the EIS graph of TFPOT-POM and PP batteries; 11 (c) is the rate performance graph of the TFPOT-POM modified battery; 11 (d) is the charge and discharge curve graph of the TFPOT-POM modified battery; 11 (e) is the long cycle performance graph of the TFPOT-POM and PP modified battery at 1 C for 500 times. DETAILED DESCRIPTION

[0016] The present invention is further described below in conjunction with the embodiments. The instruments and equipment used in the embodiments of the present invention and their models are: Shanghai Chenhua electrochemical workstation (Chenhua CHI660E) and Blue Electric Battery Test System (CT2001A).

[0017] Measured Li-S battery in the voltage range of 1.7-2.8 V, 0.1 mV·s -1Cyclic voltammetry curves at . Electrochemical impedance spectroscopy, the cycling stability at 1 C and the rate performance of Li-S batteries at different current densities were measured on a Blue Battery Test System (CT2001A).

[0018] The assembly process of the Li-S battery of the present invention comprises the following steps: 1. Preparation of C / S composites The C / S composite material was prepared using the traditional melt diffusion method; first, Super-P powder and sulfur powder were mixed at a mass ratio of 25:75 and ground thoroughly in a mortar. Then, the mixture was placed in a polytetrafluoroethylene-lined reactor and heated at 155°C for 24 hours under an argon protection atmosphere. Finally, the product was collected after cooling to room temperature to obtain a C / S composite material; 2. Preparation of conventional positive electrode C / S composite material, carbon black and PVDF with a mass ratio of 8:1:1 were mixed and ground evenly, and then 1-methyl-2-pyrrolidone (NMP) was added and stirred thoroughly to form a uniform slurry. The slurry was evenly coated on aluminum foil using a coater, and then dried at 60°C for 24 hours. After drying, the aluminum foil was cut into circular electrodes using a slicer to obtain the desired electrode; 3. Battery Assembly Before assembly, prepare all battery-related components: select CR2023 button cells as the battery model; use commercial metal lithium sheets with a diameter of 16 mm as electrodes; the electrolyte consists of a DOL / DME mixture of 1 wt% LiNO3 and 1M LiTFSI, wherein the volume fraction of DOL and DME is 1:1; cut the modified film prepared in the embodiment into diaphragm discs with a diameter of 16 mm.

[0019] The assembly of button cells must be carried out in an argon glove box to ensure that the moisture and oxygen content in the glove box are less than 1 ppm. The assembly steps are as follows: first, the prepared sulfur cathode material is placed in the cathode shell, and then an appropriate amount of electrolyte is dripped on the surface of the sulfur cathode, and the amount ratio of electrolyte to sulfur is 24 μL·mg -1 ; Then, add the cut diaphragm, and drip 40μL of electrolyte on it again, then put in the metal lithium sheet, in addition, add stainless steel gasket, shrapnel and negative electrode shell, finally, use button battery packaging machine for packaging, and let it stand for 24 hours after packaging for subsequent testing.

[0020] The preparation process of the polyoxometalate (POM) of the present invention is synthesized according to the document Angew. Chem. Int. Ed. 2023, 62, 32, e202305239, and the specific preparation process is as follows: 20.7 mmol of sodium molybdate dihydrate was dissolved in 12 mL of water, 31.0 mmol of 6.0 M HCl aqueous solution was added, and the mixture was stirred vigorously at room temperature for 1-2 minutes. Then, 10.4 mmol of tetrabutylammonium bromide in 10 ml of aqueous solution was added. After stirring for 10 minutes, the precipitate was collected by suction filtration and washed with 20 mL of water, 20 mL of ethanol, 20 mL of acetone and 20 mL of ether in sequence. 4.78 g of the crude product was dissolved in 35 mL of acetonitrile and stored at -10 °C for 24 hours to obtain (nBu4N)4[Mo8O 26 ], and then filtered to obtain transparent, colorless, blocky crystals, which were dried for 12 hours. The crystals lost their transparency during drying. 26 ]1.31mmol, (HOCH2)3CNH23.47mmol and Co(OAc)2·4H2O1.77mmol were placed in a two-necked flask, 75mL of acetonitrile was added, and after stirring and heating at 85℃ for 48h, 1.5mL of 30% hydrogen peroxide was added dropwise to the mixture, and the reaction continued overnight. After cooling, the white precipitate was removed by centrifugation, and then green crystalline polyoxometalate (POM) was obtained from the supernatant by bottle-to-bottle diffusion of ether.

[0021] Example 1 Synthesis of TFPOT-POM 8.8 mg of 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPOT), 55 mg of (nBu4N)3[CoMo6O 18 ((OCH2)3CNH2)2] (POM) was added to the Pyrex tube and mixed to obtain a mixed monomer. Then, 2 mL of N,N-dimethylformamide solution was added to the above Pyrex tube and ultrasonically shaken for 5 minutes. 0.01 mL of trifluoroacetic acid was added to the Pyrex tube as a reaction catalyst and ultrasonically shaken for 3 minutes. After that, the Pyrex tube was frozen and vacuumed three times, flame-sealed with butane gas, and heated at 100°C for 140 hours to obtain a light green powdery solid product. Next, acetone and tetrahydrofuran solution were added in turn and centrifuged and washed alternately for 3 times until the color of the washing liquid became clear. The washed solid product was placed in a vacuum at 100°C and dried for 12 hours to finally obtain a light green solid powder TFPOT-POM with a yield of 70.5%. The schematic diagram of the synthesis process of TFPOT-POM is shown in the figure. Figure 1 shown.

[0022] Example 2 Synthesis of TFPOT-POM 4.6 mg of 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPOT), 55 mg of (nBu4N)3[CoMo6O 18 ((OCH2)3CNH2)2] (POM) was added to a Pyrex tube and mixed to obtain a mixed monomer. Then, 0.5 mL of N, N-dimethylformamide solution was added to the above Pyrex tube and ultrasonically shaken for 4 minutes. 0.01 mL of trifluoroacetic acid was added to the Pyrex tube as a reaction catalyst and ultrasonically shaken for 3 minutes. Then, the Pyrex tube was frozen and vacuumed three times and flame-sealed with butane gas. After heating at 140°C for 100 hours, a light green powdery solid product was obtained. Next, acetone and tetrahydrofuran solutions were added in turn and centrifuged alternately for washing for 5 times until the color of the washing liquid became clear. The washed solid product was placed in a vacuum and dried at 80°C for 10 hours to finally obtain a light green solid powder TFPOT-POM with a yield of 65.3%.

[0023] Example 3 Synthesis of TFPOT-POM 6.7 mg of 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPOT), 55 mg of (nBu4N)3[CoMo6O 18 ((OCH2)3CNH2)2] (POM) was added to a Pyrex tube and mixed to obtain a mixed monomer. Then, 1 mL of N,N-dimethylformamide solution was added to the above Pyrex tube and ultrasonically shaken for 3 minutes. 0.01 mL of trifluoroacetic acid was added to the Pyrex tube as a reaction catalyst and ultrasonically shaken for 3 minutes. Then, the Pyrex tube was frozen and vacuumed three times and flame-sealed with butane gas. After heating at 140°C for 100 hours, a light green powdery solid product was obtained. Next, acetone and tetrahydrofuran solutions were added in sequence and centrifuged alternately for washing three times until the color of the washing liquid became clear. The washed solid product was placed in a vacuum and dried at 100°C for 10 hours to finally obtain a light green solid powder TFPOT-POM with a yield of 62.2%.

[0024] Example 4 Preparation of TFPOT-POM 10 mg of 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPOT), 55 mg of (nBu4N)3[CoMo6O 18((OCH2)3CNH2)2] (POM) was added to a Pyrex tube and mixed to obtain a mixed monomer. Then 4 mL of N,N-dimethylformamide solution was added to the above Pyrex tube and ultrasonically shaken for 3 minutes. 0.01 mL of trifluoroacetic acid was added to the Pyrex tube as a reaction catalyst and ultrasonically shaken for 3 minutes. Then, the Pyrex tube was frozen and vacuumed three times and flame-sealed with butane gas. After heating at 100°C for 120 hours, a light green powdery solid product was obtained. Next, acetone and tetrahydrofuran solutions were added in turn and centrifuged alternately for washing three times until the color of the washing liquid became clear. The washed solid product was placed in a vacuum at 100°C and dried for 12 hours to finally obtain a light green solid powder TFPOT-POM with a yield of 68.2%.

[0025] The X-ray diffraction patterns (XRD) of the TFPOT-POM powder obtained in Example 1 are as follows: Figure 2 As shown in the figure, the crystal structure of TFPOT-POM is analyzed, and the main peak of the diffraction peak is located at 5.7°, corresponding to the (100) crystal plane diffraction. The main peak diffraction intensity is high, proving that the TFPOT-POM material has a high degree of crystallinity.

[0026] Comparative Example 1 8.8 mg of 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPOT), 55 mg of (nBu4N)3[CoMo6O 18 ((OCH2)3CNH2)2] (POM) was added to the Pyrex tube and mixed to obtain a mixed monomer. Then, 2 mL of o-dichlorobenzene solution was added to the above Pyrex tube and ultrasonically shaken for 5 minutes. 0.01 mL of trifluoroacetic acid was added to the Pyrex tube as a reaction catalyst and ultrasonically shaken for 3 minutes. After that, the Pyrex tube was frozen and vacuumed three times and flame-sealed with butane gas. After heating, a light green powder solid product was obtained. Next, acetone and tetrahydrofuran solution were added in turn and centrifuged and washed alternately for 3 times until the color of the washing liquid became clear. The washed solid product was placed in a vacuum at 100°C and dried for 12 hours to finally obtain a light green solid powder TFPOT-POM with a yield of 59.4%. The obtained XRD diffraction peaks are as follows: Figure 3 shown.

[0027] Comparative Example 2 8.8 mg of 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPOT), 55 mg of (nBu4N)3[CoMo6O 18((OCH2)3CNH2)2] (POM) was added to the Pyrex tube and mixed to obtain a mixed monomer. Then, 2 mL of mesitylene solution was added to the above Pyrex tube and ultrasonically shaken for 5 minutes. 0.01 mL of trifluoroacetic acid was added to the Pyrex tube as a reaction catalyst and ultrasonically shaken for 3 minutes. After that, the Pyrex tube was frozen and vacuumed three times and flame-sealed with butane gas. After heating, a light green powder solid product was obtained. Next, acetone and tetrahydrofuran solution were added in turn and centrifuged and washed alternately for 3 times until the color of the washing liquid became clear. The washed solid product was placed in a vacuum at 100°C and dried for 12 hours to finally obtain a light green solid powder TFPOT-POM with a yield of 62.3%. The obtained XRD diffraction peaks are as follows: Figure 4 shown.

[0028] Comparative Example 3 8.8 mg of 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPOT), 55 mg of (nBu4N)3[CoMo6O 18 ((OCH2)3CNH2)2] (POM) was added to the Pyrex tube and mixed to obtain a mixed monomer. Then, 2 mL of 1,4-dioxane solution was added to the Pyrex tube and ultrasonically shaken for 5 minutes. 0.01 mL of trifluoroacetic acid was added to the Pyrex tube as a reaction catalyst and ultrasonically shaken for 3 minutes. Then, the Pyrex tube was frozen and vacuumed three times and flame-sealed with butane gas. After heating, a light green powder solid product was obtained. Next, acetone and tetrahydrofuran solution were added in turn and centrifuged and washed alternately for 3 times until the color of the washing liquid became clear. The washed solid product was placed in a vacuum at 100°C and dried for 12 hours to finally obtain a light green solid powder TFPOT-POM with a yield of 58.9%. The obtained XRD diffraction peaks are as follows: Figure 5 shown.

[0029] Comparative Example 4 8.8 mg of 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPOT), 55 mg of (nBu4N)3[CoMo6O 18((OCH2)3CNH2)2] (POM) was added to the Pyrex tube and mixed to obtain a mixed monomer. Then, 2 mL of acetonitrile solution was added to the above Pyrex tube and ultrasonically shaken for 5 minutes. 0.01 mL of trifluoroacetic acid was added to the Pyrex tube as a reaction catalyst and ultrasonically shaken for 3 minutes. After that, the Pyrex tube was frozen and vacuumed three times and flame-sealed with butane gas. After heating, a light green powder solid product was obtained. Next, acetone and tetrahydrofuran solution were added in turn and centrifuged and washed alternately for 3 times until the color of the washing liquid became clear. The washed solid product was placed in a vacuum at 100°C and dried for 12 hours to finally obtain a light green solid powder TFPOT-POM with a yield of 50.8%. The obtained XRD diffraction peaks are as follows: Figure 6 shown.

[0030] It can be seen from the above Example 1 and Comparative Examples 1-4 that different reaction solvents have a significant effect on the crystallinity and yield of the product.

[0031] The TFPOT-POM prepared in Example 1 was subjected to nitrogen isothermal adsorption measurement at 77 K to evaluate the permanent porosity and specific surface area of ​​the TFPOT-POM. Figure 7 In a, the nitrogen desorption isotherm shows an H3-type hysteresis loop, which indicates a type IV adsorption isotherm, suggesting the presence of a microporous structure, which is a characteristic of a layered structure. The (BET) specific surface area of ​​TFPOT-POM is calculated to be 40.44 m² / g. In addition, the pore size distribution (PSD) of TFPOT-POM is calculated using non-local density functional theory (NLDFT) (see Figure 7 b) shows that the average pore size of TFPOT-POM is 0.81 nm.

[0032] Figure 8 The X-ray photoelectron spectrum of the TFPOT-POM material prepared in Example 1 confirms the valence and composition of the elements in the TFPOT-POM structure. The C1s spectrum ( Figure 4 ) shows three peaks at 284.8 eV, 286.1 eV and 287.1 eV, corresponding to CC (including C=C and CC), carbon-heteroatom bonds (CO and CN) and C=N bonds, respectively. N1s spectrum ( Figure 8b) Characteristic peaks are shown at 398eV and 402eV, corresponding to primary amine and quaternary amine, respectively. A peak is shown at 400.2eV, corresponding to the C=N bond, indicating the formation of an imine bond. A peak at 399.7eV can be clearly observed in TFPOT-POM, which corresponds to the nitrogen atom in the triazine ring. In order to study the adsorption effect of TFPOT-POM on polysulfides, the XPS spectrum of TFPOT-POM after adsorbing Li2S6 was tested. The high-resolution Co 2p XPS spectrum ( Figure 8 c) Analysis shows that a peak shift occurs after Li2S6 adsorption, indicating an interaction between TFPOT-POM and LiPSs. Similar peak shifts can also be observed in the Mo3d and O 1s XPS spectra. In TFPOT-POM, the Co 2p peak shifts by 0.6 eV after adsorption. The Mo 3d peak shifts by 0.4 eV after adsorption ( Figure 8 d). The presence of oxygen atoms in the TFPOT-POM monomer facilitates the further adsorption of polysulfides. In the O 1s spectrum, the COC bond shifts toward a lower binding energy and a Li-O bond appears ( Figure 8 e). In addition, the S 2p spectra of TFPOT-POM after adsorption of Li2S6 were compared. Obviously, when TFPOT-POM is used as a catalyst, the The peak of S in TFPOT-POM T -1 (162.1eV) and S0 B (162.8eV) ( Figure 8 f) The peaks shift toward higher binding energy. These results clearly indicate that TFPOT-POM exhibits strong electrostatic adsorption, chemical catalysis, and conversion effects on LiPSs.

[0033] Example 5 Preparation of modified diaphragm (1) Dry grinding: The TFPOT-POM prepared in Example 1 was mixed with PVDF and Super-P in a weight ratio of 7:1:2, and ball-milled for 1 h to obtain a mixture; (2) Wet grinding: Add NMP solution to the mixture and ball mill for 1 h to obtain a slurry; (3) The slurry was evenly coated on the PP surface using a 40 mm four-sided sampler, and then dried in a vacuum oven at 60 °C for 12 h to obtain a diaphragm; (4) Cut the diaphragm into discs with a diameter of 16 mm, which is the TFPOT-POM modified diaphragm.

[0034] Example 6 Preparation of modified diaphragm (1) Dry grinding: The TFPOT-POM prepared in Example 1 was mixed with PVDF and Super-P in a weight ratio of 7:1:2, and ball milled for 1.5 h to obtain a mixture; (2) Wet grinding: Add NMP solution to the mixture and ball mill for 2 h to obtain a slurry; (3) The slurry was evenly coated on the PP surface using a 40 mm four-sided sampler, and then placed in a vacuum oven at 80 °C for 16 h to obtain a diaphragm; (4) Cut the diaphragm into discs with a diameter of 16 mm, which is the TFPOT-POM modified diaphragm.

[0035] Fig. 9 This is a scanning electron microscope image of TFPOT-POM / PP prepared in Example 5. The TFPOT-POM / PP composite catalyst was prepared on the PP catalyst by coating. In order to verify the cycle stability of the modified membrane, the membrane after long-term circulation was tested by scanning electron microscope. Fig. 9 a and 9b show that the TFPOT-POM / PP membrane has no obvious changes before and after the comparison cycle. In addition, the two composite membranes have completely covered the voids of the original PP membrane. Fig. 9 c It can be seen that the thickness of the composite coating is 2.81 μm.

[0036] Assembling Li-S batteries 1. Preparation of C / S composites The C / S composite material was prepared using the traditional melt diffusion method. First, Super-P powder and sulfur powder in a mass ratio of 2.5:7.5 were mixed and fully ground in a mortar. Then, the mixture was placed in a polytetrafluoroethylene-lined reactor and heated at 155°C for 24 hours under an argon protection atmosphere. Finally, the product was collected after cooling to room temperature to obtain the C / S composite material.

[0037] 2. Preparation of conventional positive electrode 80% by mass of the C / S composite material prepared above, 10% by mass of carbon black and 10% by mass of PVDF were fully mixed and ground uniformly; subsequently, 1-methyl-2-pyrrolidone (NMP) was added and stirred thoroughly to ensure the formation of a uniform slurry; the slurry was evenly coated on an aluminum foil using a coater and then dried at 60°C for 24 hours; after drying, the aluminum foil was cut into circular electrodes using a slicer to obtain the desired electrode.

[0038] 3. Battery Assembly Before assembly, all battery-related components were prepared; a CR2023 button cell was selected as the battery model; a commercial lithium metal sheet with a diameter of 16 mm was used as the electrode, and the electrolyte was composed of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) with a volume fraction of 1:1 as the solvent, 1 wt% LiNO3 and 1 M LiTFSI as the solute; HSO3 prepared in Example 6 - -ETB-COF / PP modified diaphragm, cut into 16 mm diameter pieces as diaphragm discs.

[0039] The assembly of button cells must be carried out in an argon glove box to ensure that the moisture and oxygen content in the glove box are less than 1 ppm. The assembly steps are as follows: first, the prepared sulfur cathode material is placed in the cathode shell, and then the electrolyte is dripped on the surface of the sulfur cathode, and the electrolyte and sulfur ratio is 24 μL·mg -1 , then add the cut diaphragm disc, and drip 40μL of electrolyte on it again, then put in the metal lithium sheet, in addition, add stainless steel gasket, shrapnel and negative electrode shell; finally, use button battery packaging machine for packaging, and let it stand for 24 hours after packaging for subsequent testing.

[0040] Fig.10 The electrochemical catalytic performance of TFPOT-POM as a separator material for lithium-sulfur (Li-S) batteries was evaluated. First, a typical cyclic voltammetry (CV) measurement was performed on the material in the voltage window of 1.7-2.8 V at a rate of 0.1 mV·s -1 Their electrochemical behaviors were analyzed at a scan rate of Fig.10 The CV curve of POT-POM in a shows the characteristic redox peaks of Li-S batteries. During the scan, the two obvious reduction peaks at 2.25V and 2.01V correspond to the conversion of S8 to soluble long-chain polysulfides (LiPSs), followed by further reduction to the final products (Li2S2 and Li2S). During the scan, the two oxidation peaks at 2.35V and 2.43V represent the conversion of Li2S to Li2Sn (2≤n≤8), and finally to S8. This is attributed to the reduction of polarization and the acceleration of reaction kinetics.

[0041] from Fig.10 In the electrochemical impedance spectroscopy (EIS) data shown in Figure b, the bulk resistance (Rb) values ​​of TFPOT-POM and PP separators are 3.35Ω and 4.71Ω, respectively, and the corresponding ionic conductivity ( Fig.10 c) 1.32 and 1.99 mS·cm respectively -1 The enhancement of the ionic conductivity of TFPOT-POM may be attributed to the catalytic conversion promoted by the oxygen atoms in the aldehyde monomers and polyacids, which is beneficial to the Li + Transmission. +The mobility number reflects the interaction with lithium salt anions and polysulfide anions, based on chronoamperometry and EIS data ( Fig.10 d) Calculation. Li of TFPOT-POM and PP + The transference numbers are 0.987 and 0.648, respectively. These results indicate that the active oxygen atoms in TFPOT-POM anchor the anions in the lithium salt dissociation and polysulfide, thereby accelerating the Li + Since the nucleation and dissolution of Li2S usually have the highest energy barriers in the charge and discharge reactions of lithium-sulfur (Li-S) batteries, they are the rate-limiting steps in the redox process. To further clarify the role of TFPOT-POM in the solid-liquid transformation of polysulfides, constant potential charge-discharge experiments were performed to study the electrochemical transformation kinetics of Li2S ( Fig.10 e). Specifically, the constant potential discharge curves of Li2S deposition show that the TFPOT-POM separator (542 s, 84.5 mAh g -1 ) has a very early nucleation and growth response time (638 s) and a higher deposition capacity (51.46 mAh g -1 ), which indicates that the presence of oxygen atoms improves the conversion efficiency from polysulfide to Li2S and accelerates the deposition kinetics of Li2S. In addition, a symmetric cell using TFPOT-POM and PP separator containing Li2S6 electrolyte was tested ( Fig.10 f). Due to poor conductivity and weak interaction with LiPSs, the CV curve of PP separator shows low current density and large polarization, resulting in slow conversion kinetics of LiPSs. In contrast, TFPOT-POM exhibits higher current density and lower polarization, showing excellent catalytic activity for polysulfide conversion, which is attributed to its strong adsorption capacity for polysulfides and high catalytic activity of polyacids.

[0042] In order to further study the effect of COF-modified separator on the performance of lithium-sulfur batteries, CR2025 button cells were assembled and the voltage was adjusted within the voltage window of 1.7-2.8 V at a rate of 0.1 mV·s -1 Typical cyclic voltammetry (CV) measurements were performed in the first three cycles at a scan rate of Fig.11 a) to analyze the electrochemical behavior. The CV curves of the second and third cycles overlap, indicating that the TFPOT-POM separator has good redox reversibility during the charge and discharge process. Fig.11 As shown in b, the charge transfer resistance (Rct) of the TFPOT-POM modified separator battery is significantly lower than that of the PP separator, indicating that the charge transfer performance and redox kinetics have been improved. This modification also brings unique oxidation behavior, enhances the electrochemical reaction kinetics and reduces the energy barrier. Fig.11As shown in c, the TFPOT-POM modified separator exhibits excellent rate performance. The discharge capacities at 0.1, 0.2, 0.5, 1, and 2 C are 1033, 933, 823, 727, and 618 mAh·g, respectively. -1 When the current density is restored to 0.1 C, the capacity can be restored to 912 mAh g -1 The charge-discharge curves in 11d show that even at a high rate of 2 C, the TFPOT-POM battery still exhibits two typical discharge platforms.

[0043] Long-term cycle tests were conducted on lithium-ion batteries with TFPOT-POM and PP separators. Fig.11 As shown in e. At a rate of 1 C, the TFPOT-POM battery experienced 500 cycles. The initial capacity was 844 mAh g -1 After 500 cycles, the capacity remains at 643 mAh g -1 , the corresponding capacity decay rate is 0.047%. In contrast, the capacity decay rate of PP separator after 500 cycles is 0.076%.

[0044] The above embodiments are only partial implementation schemes of the present invention, but the protection scope of the present invention is not limited thereto. The various aspects and implementation schemes of the present invention disclosed herein are only examples of specific ways to make and use the present invention. The present invention is not limited to any limitation due to the sequence and specific operations of the embodiments. Any replacement and changes that can be easily thought of by any researcher familiar with the technical field within the technical scope disclosed by the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a polyacid-based covalent organic skeleton modified diaphragm, characterized in that: The following steps are involved: S1. Synthesis of TFPOT-COF 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPOT) and polyoxometalate (POM) salt are placed in a Pyrex tube and mixed to obtain a mixed monomer, and then N,N-dimethylformamide solution is added, ultrasonically shaken, and then a catalyst is added and ultrasonically shaken, and then the freezing and vacuuming process is repeated three times, flame-sealed with butane gas, heated to obtain a solid product, and then washed and vacuum-dried to obtain TFPOT-POM; The molecular formula of the polyoxometalate (POM) is ( n Bu4N)3[CoMo6O 18 ((OCH2)3CNH2)2]; S2. Preparation of modified diaphragm TFPOT-POM, PVDF and Super-P were mixed and ball-milled for 1-1.5 hours to obtain a mixture; N-methylpyrrolidone solution was added to the mixture and ball-milled for 1-2 hours to obtain a slurry; the slurry was coated on the surface of PP, vacuum-dried, and the obtained diaphragm was cut into discs with a diameter of 16 mm to obtain a modified diaphragm.

2. The method for preparing the polyacid-based covalent organic skeleton modified diaphragm according to claim 1, characterized in that: The mass ratio of 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPOT) to polyoxometalate (POM) in step S1 is (2-6):

25.

3. The method for preparing the polyacid-based covalent organic skeleton modified diaphragm according to claim 1, characterized in that: The dosage of 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPOT) and N,N-dimethylformamide in step S1 is (1-8) mg / mL, and the ultrasonic oscillation time is 3-5 min.

4. The method for preparing the polyacid-based covalent organic skeleton modified diaphragm according to claim 1, characterized in that: The catalyst in step S1 is trifluoroacetic acid, and the dosage of trifluoroacetic acid and 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPOT) is 0.001-0.0025 mL / mg; the mass fraction of the trifluoroacetic acid is not less than 99%.

5. The method for preparing the polyacid-based covalent organic skeleton modified diaphragm according to claim 1, characterized in that: The heating temperature in step S1 is 100-140° C., and the heating time is 100-140 hours.

6. The method for preparing the polyacid-based covalent organic skeleton modified diaphragm according to claim 1, characterized in that: The specific process of washing in step S1 is: adding acetone and tetrahydrofuran solution in sequence and washing by alternating centrifugation for 3-5 times; the temperature of vacuum drying is 80-120° C., and the time of vacuum drying is 10-12 hours.

7. The method for preparing a polyacid-based covalent organic skeleton modified diaphragm according to claim 1, characterized in that: The weight ratio of TFPOT-POM, PVDF and Super-P in step S2 is 7:1:

2.

8. The method for preparing the polyacid-based covalent organic skeleton modified diaphragm according to claim 1, characterized in that: The vacuum drying temperature in step S2 is 60-80° C., and the vacuum drying time is 12-16 hours.

9. A polyacid-based covalent organic skeleton modified diaphragm obtained by the preparation method according to any one of claims 1 to 8.

10. A lithium-sulfur battery comprising the polyacid-based covalent organic skeleton modified diaphragm according to claim 9.

Citation Information

Patent Citations

  • Polymetallic oxygen cluster-based covalent organic frame material as well as preparation method and application thereof

    CN110724166A

  • Preparation method of polyoxometallate / covalent organic framework material and application of same in styrene air epoxidation reaction

    CN111905822A

  • Polyoxometallate-covalent organic framework composite material as well as preparation method and application thereof

    CN118527179A

  • Method for preparing ionic covalent organic framework modified lithium-sulfur battery modified diaphragm, modified diaphragm and battery containing modified diaphragm

    CN118539085A

  • Method for modifying diaphragm and lithium-sulfur battery based on metal organic framework defect structure

    CN118983613A